Comparison of Simple Additive Weighting and Profile Matching Methods in Scholarship Recipient Selection - Fitri Handayani (Institute of Computer Science (IOCS), 2021)
Private Universities organize scholarship programs that are given to prospective scholarship recipients with the aim of being able to help reduce the cost of education. So it is necessary to make the correct and targeted selection. However, the selection of scholarship recipients is still done manually. This can be done with accurate analysis. This study aims to determine the best algorithm of the two methods compared, namely Simple Additive Weighting and Profile Matching. The assessment criteria used consisted of parents' income, home owner status, parents' home condition, number of dependents and parental status. The results of the study using the Profile Matching method produced an accuracy of 100% while the Simple Additive Weighting method produced an accuracy of 96%.